Ten Steps to Develop Patient Education Videos for Individuals of All Health Literacy Levels. (2nd September 2014) - Saffarzadeh, Areo G.; Verma, Sunil P.
Abstract : Objectives: (1) Create a protocol for developing educational videos for patients of all health literacy levels. (2) Describe National Institutes of Health (NIH) guidelines, evidence‐based principles of instructional design, and industry best practices related to creating educational videos for patients. Methods: Utilizing (1) NIH guidelines for patient education materials, (2) evidence‐based principles of instructional design, and (3) industry best practices, a 10‐step protocol was developed for creating video‐based patient education materials. As a proof‐of‐concept, these 10 steps were used to create a short video to help patients understand flexible laryngostroboscopy. Results: Using NIH guidelines, a script was created with text designed for the sixth‐grade reading level using the SMOG Readability Formula. Evidence‐based principles of instructional design that were incorporated into the video included: the Personalization Principle, Multimedia Principle, Coherence Principle, Contiguity Principle, and Practice Principle. A video was recorded with a high definition camera, and audio narration was recorded separately. A short video describing laryngeal anatomy and showing actual footage laryngostoboscopy was edited on Camtasia Studio 8.0 and produced for optimized viewing on the iPad. The video was pilot tested on patients prior to undergoing flexible laryngostroboscopy at an outpatient otolaryngology–head and neck surgery clinic. Conclusions: There is currently no protocol for creating educational videos for patients with limited health literacy. This 10‐step protocol was created to help those creating educational videos incorporate NIH guidelines, evidence‐based principles of instructional design, and industry best practices into their projects.